2020
DOI: 10.1002/lsm.23344
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Human and Porcine Skin in Laser‐Assisted Drug Delivery of Chemotherapeutics

Abstract: Background and Objectives Porcine skin is a widely used model in diffusion studies, but its usefulness for laser‐assisted drug delivery (LADD) has not been evaluated in comparison with human skin. This study compared porcine and human skin in ex vivo LADD diffusion studies. Study Design/Materials and Methods Ex vivo ablative fractional laser (AFL) treatments (5, 20, and 80 mJ/mb) were applied to skin samples from three sources: human, normal pig (Duroc × Landrace × Yorkshire breed), and a hyperkeratotic pig ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In their study, they observed a deeper laser channel depth of 70 µm using OCT. The epidermal thickness was not measured in the ICG-delivery study, but a recent study found a median depth of 76 µm in abdominal human skin [ 25 ]; thus, the channels might not penetrate through the epidermis similar to our study on pig skin. The different channel depths could be due to differences in the hydration of the skin, the resolution of the OCT or deviations in the laser beam angle to the focal plane of the skin, which has been shown to have a great impact on the laser channel morphometrics [ 26 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In their study, they observed a deeper laser channel depth of 70 µm using OCT. The epidermal thickness was not measured in the ICG-delivery study, but a recent study found a median depth of 76 µm in abdominal human skin [ 25 ]; thus, the channels might not penetrate through the epidermis similar to our study on pig skin. The different channel depths could be due to differences in the hydration of the skin, the resolution of the OCT or deviations in the laser beam angle to the focal plane of the skin, which has been shown to have a great impact on the laser channel morphometrics [ 26 ].…”
Section: Discussionsupporting
confidence: 71%
“…One recent study investigated the delivery of the fluorescent molecule indocyanine green (ICG) with a fractional CO 2 laser also using 2.5 mJ/mb and 5% density. Even though they used ex vivo human skin [ 24 ], it was shown that drug biodistribution among human and pig skin is similar [ 25 ]. In their study, they observed a deeper laser channel depth of 70 µm using OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies were embedded in water, cryosectioned in 10 µm vertical samples, and stored at −80°C until MALDI‐MSI analysis. The distribution of 5‐FU was qualitatively determined by the same MALDI‐MSI method as described previously by the authors 23 . The samples were imaged on a QExactive Orbitrap mass spectrometer (Thermo Fischer Scientific) equipped with a SMALDI5 ion source (TransMIT GmbH).…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of 5-FU was qualitatively determined by the same MALDI-MSI method as described previously by the authors. 23 The samples were imaged on a QExactive Orbitrap mass spectrometer (Thermo Fischer Scientific) equipped with a SMALDI5 ion source (TransMIT GmbH). Imaging was performed in line mode at a pixel size of 20 µm using a scan range of m/z 127-900 in negative-ion mode.…”
Section: (6) Visualization Of Drug Biodistribution By Maldi-msimentioning
confidence: 99%
“…When used to treat BCCs, intralesional BLM is currently administered by conventional needle injection (NI) to overcome the skin barrier. Several alternative drug delivery systems that may be used to treat BCCs have been tested, including hollow micro-needles (Sabri et al, 2020 ), pneumatic injection (Erlendsson et al, 2020 ; Bik et al, 2021 ; Rosenberg et al, 2021 ), and laser-assisted drug delivery (LADD) (Wenande et al, 2021 ). Ablative fractional laser (AFL) has been shown to facilitate and enhance topical BLM delivery via LADD ex vivo and is a prime candidate for BLM drug delivery due to its intrinsically therapeutic effect on BCCs (Mirza and Khatri, 2017 ; Hendel et al, 2019 ; Navarrete-Dechent, 2019 ).…”
Section: Introductionmentioning
confidence: 99%